A New Test for Ridge Wind Directional Data Under Neutrosophic Statistics - Aslam, Muhammad; Al-Marshadi, Ali Hussein (Frontiers in Energy Research, 2022)
The statistical tests under classical statistics can be only applied when the data is linear and has certain observations. The existing statistical tests cannot be applied for circular/angles data. In this paper, the Watson-Williams test under neutrosophic is introduced to analyze having uncertain, imprecise, and indeterminate circular/angles data. The neutrosophic test statistic is introduced and applied to wind direction data. From the real example and simulation study, it can be concluded the proposed neutrosophic Watson-Williams test performs better than the Watson-Williams test under classical statistics.